2024
DOI: 10.1186/s12903-024-04229-2
|View full text |Cite
|
Sign up to set email alerts
|

Application of sticky bone combined with concentrated growth factor (CGF) for horizontal alveolar ridge augmentation of anterior teeth: a randomized controlled clinical study

Yu Xie,
Yanyan Qin,
Miao Wei
et al.

Abstract: Objective This study was designed to estimate the effect of sticky bone combined with concentrated growth factor (CGF) on anterior alveolar horizontal augmentation during implantation. Methods Twenty-eight patients were randomly assigned to either the test group (Group 1, n = 14) or the control group (Group 2, n = 14). Patients in Group 1 and Group 2 underwent GBR using sticky bone combined with CGF and bone powders mixed with saline, respectively.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…A study involving 28 patients found that using sticky bone and CGF combined during anterior alveolar horizontal augmentation was more effective than conventional GBR [ 29 ]. The three-dimensional architecture and mechanical characteristics of three combinations of autologous platelet liquid (APL), blood, or physiological water, and composite bovine graft, were assessed in a previously conducted in vitro study [ 30 ].…”
Section: Reviewmentioning
confidence: 99%
“…A study involving 28 patients found that using sticky bone and CGF combined during anterior alveolar horizontal augmentation was more effective than conventional GBR [ 29 ]. The three-dimensional architecture and mechanical characteristics of three combinations of autologous platelet liquid (APL), blood, or physiological water, and composite bovine graft, were assessed in a previously conducted in vitro study [ 30 ].…”
Section: Reviewmentioning
confidence: 99%